Investigating Students’ Eyesights in the Utilization of Platforms in Learning ESP During the Covid-19 Pandemic - Multazam Abubakar; Annisa Shofa Tsuraya (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2021)
The Covid-19 pandemic suddenly attacked the world and led every sector of life affected, including the education process, which is forced to shift into online mode. All educators are forced to adapt and find a learning platform to utilize in this emergency remote learning. This research uncovers the students' preference of digital platforms in learning ESP during the Covid-19 pandemic, the factors accepting their preference, and their perception of those learning platforms. The design of this study is qualitative. The participants of this study were 112 freshmen of a state university in Makassar who learn English for Specific Purposes (ESP), comprising 95 females and 17 males. The participants were consisted of 3 majors and involved in remote learning for one semester (16 meetings) through WhatsApp, Google Classroom, University LMS, YouTube, and Video Conference (Zoom and Google Meet). In order to collect the data, a questionnaire that consists of close-ended and open-ended questions was distributed to the participants. It is found that the students' preference of digital platform in learning ESP during the Covid-19 pandemic is WhatsApp. The factors affecting students' preference of the platform are demographic and economic constraints. The criteria of the application that is highly preferred by the students were the one which does not drain the internet quota, can still work correctly in which the internet connection is not strong, and can facilitate the interaction between lecturers and students. Finally, this study suggests that no one perfect digital platform can replace face-to-face learning since many things are missing during this online learning. So, to keep it running effectively, the combination of several platforms is required to be utilized.